The changing IT trends: are academic libraries coping? - Musoke, Maria G. N.; Sentamu, Timothy; Mwesigwa, Andrew (Qualitative and Quantitative Methods in Libraries; Vol 3 No 4 (2014): December 2014 Issue, 2017)
The modern academic library environment is changing not only to cope with technological advancements, but also to organise, preserve and make knowledge accessible in real time. The current technological developments, the increased library user expectations and users‟ participation in the information chain e.g through social media have been the major catalysts for automation. By 2013, Makerere University (Mak) Main Library alone had over 474 Personal Computers (PCs) in its bid to integrate Information Technologies (ITs) in library functions. However, in recent times, there has been evidence of own laptops‟ usage by Mak Library users. In response to this trend, Mak Main library redesigned space in 2012 to provide data points to accommodate laptop users as the wireless connection infrastructure could no longer handle the exponentially increased user population at Mak library. The paper reports findings of a quantitative study that investigated the usage of the Main library IT facilities, users‟ preferences and whether the various IT facilities were meeting the users‟ needs and expectations.  The findings revealed that 22% (1221) of the 5,472 library users, at the time of collecting data, were found using library IT facilities, while the rest of the library users 78% (4,251) were engaged in private study, discussions in the Group study facilities or were using other library facilities and services.  The 22% found using library IT facilities reported to have used the following: 46% Learning Commons for undergraduates, 4% Research Commons for postgraduates and researchers, 16% OPAC terminals, 2% lab for users with disabilities, 10% laptop users‟ lab and 22% own laptops connected to the LAN in the rest of the Main library building. Of the 22% who used library IT facilities, only 38% owned laptops, hence confirming the continued need for library PCs. The study highlighted reasons for the preferred IT facilities and its implications for policy on academic library service delivery. The findings confirmed that Mak Main lib had tried to cope with the changing IT developments and user behavior to remain relevant to the academic and research community served.